2008
DOI: 10.1007/s11240-008-9383-z
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-mediated transformation of the winter jujube (Zizyphus jujuba Mill.)

Abstract: Winter jujube, a species that originated in China, is the most prominent elite variety of jujube (Zizyphus jujuba Mill.). Due to its economic value and its recalcitrance to improvements through traditional plant breeding approaches, genetic transformation techniques may have a great potential in providing the means to transfer one or more selected desirable traits into the plant genome. We reported here an improved protocol for the Agrobacterium-mediated transformation of shoot tips of winter jujube. We have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…4). It has been suggested that a vacuum pump creates a negative pressure environment that results in an increase in effective Agrobacterium volatilization, a condition conducive to the transfer of a foreign gene into plant cells (Gu et al 2008). Vacuum treatment of shoot apices with Agrobacterium for more than 30 min resulted in explant tissues being completely colonized by the Agrobacterium, making it more difficult to eliminate it in the recovery and subsequent stages resulting in loss of shoot apices and subsequent growth (data not shown).…”
Section: Vacuum Infiltration Of Shoot Apices With Agrobacteriummentioning
confidence: 98%
See 2 more Smart Citations
“…4). It has been suggested that a vacuum pump creates a negative pressure environment that results in an increase in effective Agrobacterium volatilization, a condition conducive to the transfer of a foreign gene into plant cells (Gu et al 2008). Vacuum treatment of shoot apices with Agrobacterium for more than 30 min resulted in explant tissues being completely colonized by the Agrobacterium, making it more difficult to eliminate it in the recovery and subsequent stages resulting in loss of shoot apices and subsequent growth (data not shown).…”
Section: Vacuum Infiltration Of Shoot Apices With Agrobacteriummentioning
confidence: 98%
“…600 1.2 (Table 1). A reduction in the mean transformation frequency was observed following inoculation with higher densities of Agrobacterium cells, possibly because of increased production of toxins to the receptor cells (Gu et al 2008). Several workers reported the optimum cell density for Agrobacterium-infection in O.D.…”
Section: Cell Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Agrobacteriummediated gene transfer is known as the method of choice to produce transgenic plants with a low copy number of introduced genes and other advantages (Hiei et al 1997). At present, stable Agrobacterium-mediated transformation protocols have been reported in Vitis (Nakano et al 1994;Scorza et al 1995;Li et al 2008;Dhekney et al 2009) and many other woody species (Cervera et al 1998;Joseph Lopez et al 2004;Li et al 2007a, b;Gu et al 2008;de Oliveira et al 2009;Jube and Borthakur 2009). However, there has been, to date, no available published report of the successful genetic transformation of P. tricuspidata by Agrobacterium mediation or any other methods.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, Zizyphus jujuba, as the main constructive species, has enormous potential to help restore vegetation on shell island beach ridges (Xia et al 2009;Tian et al 2011). Recent studies on Z. jujuba have been mainly focusing on seedling cultivation, flower organ and anatomical characteristics (Niu et al 2011), vegetative propagation technology (Danthu et al 2004), agrobacteriummediated transformation technology (Gu et al 2008), soil moisture balance, water competition evaluation (Zhao et al 2012), and antioxidant effects of sarcocarp, seed, and leaf (Kim & Son 2011). Research on Z. jujuba drought physiology has mainly been concentrating on the diurnal dynamics of osmotic adjustment substances, biomass, waterconsumption characteristics, and protective enzyme and photosynthetic characteristics under only three to four levels of water stress (Zhou et al 2010(Zhou et al , 2011.…”
Section: Introductionmentioning
confidence: 99%